2018
DOI: 10.1007/s00068-018-0969-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of injury and outcomes in the elderly patient with rib fractures: a multicenter observational study

Abstract: Pneumonia and death occur in about 10% of elderly patients with rib fractures. Apart from the severity of thoracic injuries, the presence and severity of extra-thoracic injuries and cardiopulmonary comorbidities are associated with poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 15 publications
1
39
0
1
Order By: Relevance
“…In severe cases, the rib fragments harm the inner organs, such as the lungs, the liver, the kidneys, or the spleen [1,3,9,11,12]. Since rib fractures are often related to specific intrathoracic and intraabdominal traumas, predictions of the probability, progression, and complication rate of the inner organ injuries are possible [12–15]. Detailed knowledge about the fracture patterns of serial rib fractures is therefore essential to improve the treatment strategy of these types of injury.…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, the rib fragments harm the inner organs, such as the lungs, the liver, the kidneys, or the spleen [1,3,9,11,12]. Since rib fractures are often related to specific intrathoracic and intraabdominal traumas, predictions of the probability, progression, and complication rate of the inner organ injuries are possible [12–15]. Detailed knowledge about the fracture patterns of serial rib fractures is therefore essential to improve the treatment strategy of these types of injury.…”
Section: Introductionmentioning
confidence: 99%
“…In elderly patients aged 65 years or older, over 50% have sustained rib fractures following low-energy trauma (LET) such as a fall from standing height [6,7]. The number of rib fractures, pre-existent pulmonary pathology, and age are known risk factors for rib fracture-associated mortality and morbidity [2][3][4][7][8][9][10][11][12][13]. Rib fractures are the most common fractures in men and second most common in women over 65 years [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, concomitant injuries of the thoracic cage had no statistical impact on clinical outcome scores. In contrast, several studies reported negative effects of thoracic cage injuries such as serial rip fractures in the elderly [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%